AN APPROACH TO UNDERSTANDING MAN FROM THE PERSPECTIVE OF DUALISM AND MONISM - Bozorov Sukhrob; J.SH.Mustafayev (Лучшие интеллектуальные исследования, 2024)
Abstract: The approach to human understanding through the perspectives of dualism and monism is one of the important topics of philosophy. These approaches influence how we understand the human self and the relationship between mind and body.